Construindo a confiança nos órgãos públicos: o caso do IBGE - ALEX DE ALMEIDA UCHÔAS (2021)
The object of this work is the Brazilian Institute of Geography and Statistics Foundation. The general objective is to create an index for measuring the confidence of the population in a Public Institution, proposing a model that explains the antecedents and consequences of measured confidence. Trust, portrayed here after the literature review, reflects two aspects of the Foundation's work, first the trust in the security of the data reported to IBGE and, second, the respondent's trust in the data that are published by IBGE. Trust, as shown in the dissertation, is a multidisciplinary concept, which does not have a single definition. For this dissertation, trust was conceptualized on one side because of a firm belief that another party has a high level of integrity and honesty, so the division of the construct as stated above. To meet the objective of this dissertation, it was also necessary to research the antecedents and consequences of trust, through the literature review, a model was proposed that proposed the perceptions of respondents regarding the capacity, integrity, benevolence, transparency, and knowledge of the IBGE, in addition to their previous experiences with the Institute would positively influence trust in the institution. Consequently, we studied the gains that trust would bring to IBGE through the intentions of respondents to the Institute. Information was collected by means of an electronic questionnaire, made available by several digital media, limited to Mato Grosso do Sul residents aged at least 18. The study was characterized as descriptive and quantitative with a confirmatory character. The methods chosen for the analysis and for the validation of the proposed hypotheses were the structural equation modeling (SEM) and the partial least squares analysis (PLS), respectively. It should be noted that, according to the results of this study, 63% of the respondents trust the security of the data passed on to IBGE, while 71% trust the veracity of the data released by the Institute. Considering the statistical analyzes made regarding the equalization of the sample in relation to the expected education, these numbers would drop to 25% and 42%, respectively. The results also demonstrate that Previous Experiences classified as positive and the interviewee's perception of benevolence from IBGE has a direct and relevant relationship with one of the two constructs of trust studied, security and veracity, respectively. The perception of capacity, integrity and transparency demonstrated a relevant and direct relationship with both constructs of trust in IBGE. The only construct that had no impact on the faith in the Institute was that of perceived knowledge. The model also shows that there is a strong relationship between the respondent's confidence and availability to answer IBGE surveys if requested, and the willingness to not criticize the data released by the organization. Some characteristics of the respondents were analyzed, outside the model, relating them to the confidence index. These analyses, among other results, revealed that schooling has a strong relationship with the confidence constructs. It is also noteworthy, despite the average effect shown in the statistical analyses, that the way the interviewee obtains information may influence trust in the Institute. Among those respondents who do not trust the veracity of the IBGE data, 52% get a lot of information via Twitter, and 87% acquire much information by messaging apps, like 'WhatsApp' and 'telegram'. Finally, in the face of all academic and managerial implications presented, an action plan was proposed that aims to list a series of steps to increase the population's trust in the IBGE, in its two aspects.